PENGARUH PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION BERBASIS CONTEXTUAL TEACHING AND LEARNING - Nurhayati, Dian; Saputro, Subiyanto Hadi; R.S, Sri Mantini (Universitas Negeri Semarang, 2013)
The aim of this research is to determine the effect of Cooperative Integrated Reading and Composition based Contextual Teaching and Learning. This research population is XI Sciences of senior high school 1 brebes 2011/2012. First data analysis showed that the population data are normally distributed and homogeneous, so the sampling technique which used is cluster random sampling. From the result of the draws, XI Science-1 as an experiment class (Cooperative Integrated Reading and Composition Based contextual Teaching and Learning) and XI Science-5 as a control class (conventional learning). Final data analysis showed that learning product both classes are normally distributed and have equal variances. In the test of correlation, obtained 0,732 of rb value, which showed a height correlation, so Cooperative Integrated Reading and Composition Based Contextual Teaching and Learning has height effect on student learning product in colloids. This learning contributes to student learning product=54%. The learning product of experiment and control class had reached completeness. classical learning completeness which achieved by experiment and control class are respectively 95% and 87,5%. The average value of affective and psychomotor in experimental class is better than the control class. Based on this research, we can conclude that Cooperative Integrated Reading and Composition based Contextual Teaching and Learning assisted has a positive effect on learning product in senior high school 1 brebes.